2014
DOI: 10.1519/jsc.0000000000000445
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Anthropometry and Performance, and Their Interrelationships, Across Three Seasons in Elite Youth Rugby League Players

Abstract: This study investigated changes in anthropometry and performance, and their interrelationships, across three consecutive seasons (under-15 to under-17

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 42 publications
(42 reference statements)
1
44
0
1
Order By: Relevance
“…Linear speed data for elite youth rugby league players over 10, 20, 30, 40 and 60 m are presented in Table 2. Linear speed has been shown to differentiate between age categories within some studies [17, 20, 2326] but not others [19, 21]. Differences between playing level [13, 2428] and playing position [17, 21, 24, 26, 39, 43] have consistently been identified, highlighting greater speed in elite compared to sub-elite players, and backs compared to forwards.…”
Section: Linear Speedmentioning
confidence: 99%
See 4 more Smart Citations
“…Linear speed data for elite youth rugby league players over 10, 20, 30, 40 and 60 m are presented in Table 2. Linear speed has been shown to differentiate between age categories within some studies [17, 20, 2326] but not others [19, 21]. Differences between playing level [13, 2428] and playing position [17, 21, 24, 26, 39, 43] have consistently been identified, highlighting greater speed in elite compared to sub-elite players, and backs compared to forwards.…”
Section: Linear Speedmentioning
confidence: 99%
“…Height and body mass have been shown to increase with age in elite [17, 1923] and sub-elite players [24, 25], are greater within elite compared with sub-elite levels [13, 2628], and are higher in forwards than backs [17, 21, 29, 30]. Findings in elite players aged between 13 and 15 years [17] showed that 92.4 and 33.3% of players were taller and 96.0 and 30.3% were heavier than the UK 50th and 97th growth percentiles, respectively [31].…”
Section: Anthropometric Qualitiesmentioning
confidence: 99%
See 3 more Smart Citations